The Effect of Working Capital Turnover and Liquidity on Profitability, with Leverage as an Intervening Variable. (A Study of Manufacturing Companies Listed on the Indonesia Stock Exchange in 2021-2023) - Rozi Destian; Fesaraweny Fesaraweny; Windy Kusumahati; Habibah Muharmi (Jurnal Multidisiplin Sahombu, 2026)
This research is motivated by the importance of manufacturing companies' ability to manage working capital and liquidity to increase profitability amidst increasingly fierce industrial competition, as well as the role of leverage as a funding mechanism that can strengthen or weaken financial performance. The purpose of this study is to analyze the effect of working capital turnover and liquidity on profitability, with leverage as an intervening variable, in manufacturing companies listed on the Indonesia Stock Exchange during the 2021–2023 period. This study uses a quantitative approach with secondary data analysis methods obtained from the companies' annual financial reports. The research sample was determined using a purposive sampling technique based on certain criteria. Data were analyzed using the Partial Least Squares (PLS) method to test the direct and indirect effects between variables. The results show that profitability has a positive effect on company financial performance, while liquidity tends to have a negative effect on profitability. Working capital turnover plays a crucial role in supporting company operational efficiency and contributing to increased profits. These findings indicate that optimal working capital and liquidity management are essential for companies to improve their financial performance sustainably. This research is expected to be a consideration for company management and investors in making financial decisions. The conclusion of this study shows that effective working capital and liquidity management, accompanied by an optimal leverage structure, can increase the profitability of manufacturing companies in a sustainable manner.